Supplementation, through the diet of broilers, an Emulsifier-Suñactant - Cajusol Baldera, Edith Verónica (2016)
One hundred chicks Cobb 500 one day old, ofboth sexes, were used in a feeding trial in which the effect of the inclusion of an emulsifier-surfactant product in the diet on the food consumption, increase of live weight, weight and performance of housing, feed conversion and economic merit. The product used is supplier of fosfatidil hill, smooth fosfatidil hill and polyethylene glycol ricinoleato. The following treatments were evaluated: Tl, witness; T2, 0.025 %; T3, 0.05 %; T4, 0.075 % of the product. The analysis showed that the product was better used to live weight gain in younger age of the chickens; feed conversion was 13% more efficient and economic merit 11 % more efficient in treatment 2 compared with the control. Weight and carcass yield did not reach statistical significance for differences but the trend was to improve the product. It is advisable to use the product in the proportion of 0.025% in the diet of broilers; likewise, evaluate it in other birds and mammals.